Older people as equal partners in designing a digital device for senior's everyday needs - Sustar, Helena; Jones, Sara; Zaphiris, Panayiotis (My University, 2009)
In this paper, we describe use of a User Centred Design (UCD) process, including Cultural Probes and creative workshops, intended to stimulate everyday creativity in designers and older people designing digital devices for seniors everyday needs.